Transformasi Persidangan Pidana: Model Keadilan Restoratif PN Wamena - Saifullah Anwar; Irna Irna; Simon Marian; Jimince Jimrianita Kogoya (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
Justice is a necessity and hope for justice seekers. In the criminal context, restorative justice is needed where judges play an important role in enforcing it. This study aims to explain the ideal practice of trial based on restorative justice. This study uses a qualitative approach with the type of empirical research through in-depth interviews. The research population is apparatus at the Wamena District Court with three categories of samples, namely key informants, main and supporters. The results of the study show that the ideal practice of restorative justice for judges is by presenting victims through online trial means or victims can be represented by heirs or who is appointed based on a special power of attorney. The judge can give the defendant the opportunity to contact the family at trial, and can present the defendant's family at trial. In addition, judges can involve traditional or community leaders so that communication can run effectively and efficiently.